A RECENT REVIEW ON THE FAILURE ANALYSIS OF BOILER TUBE - Utomo, Faris Fadhil; Rashyid, Muhammad Ibnu; Nugraha, Ariyana Dwiputra; Muflikhun, Muhammad Akhsin (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The failure analysis in the industrial systems i.e. power plan, oil, and gas companies, has been reported by many researchers. One of the most reported has occurred in the Boiler system. Among the components of the boiler, problems, and failures often took place in the tube. The purposes of the recent study are to describe, classify, and review the latest update of the failure behavior of the boiler tube. The failure was formed by overheating, creep, stress corrosion, cracking, erosion, oxidation, and post-weld heat treatment (PWHT). The current works are listed based on the methods used to identify the failures, failure observations, and case studies updated from the boiler tube failure condition. The research suggests that to replace the failure tubes, analysis related to the stress induced outside and inside the tube, environment conditions, and lifetime maintenance works need to be considered.